Water Footprint Analysis of Different Techniques of Cocoa Propagation - Santosa, Edi; Supijatno, Supijatno; Wachjar, Ade; Rohman, Fadil; Abdoellah, Soetanto (Department of Agronomy and Horticulture, IPB University, 2023)
The nursery phase plays a crucial role in rejuvenating cocoa plantations as it significantly impacts the quality and productivity of the mature trees in the field. However, despite its significance, there remains a lack of understanding regarding its contribution to the water footprint (WF) in cocoa production. This study aims to assess the WF of various propagation techniques to promote sustainable nursery practices. Data on nurseries were collected at the Indonesian Coffee and Cocoa Research Institute in Jember, East Java, Indonesia, from June 2017 to January 2018. The results revealed that propagation accounted for a total WF ranging from 74.28 to 319.41 m3.ha-1 of established cocoa trees, with an average of 186.68 m3. This total WF consisted of 9.02 to 12.89 m3 (7.69%) attributed to seed production and 61.39 to 283.34 m3 (92.30%) attributed to the nursery phase. Among the different nursery techniques studied, the production of true seedlings exhibited the lowest WF, followed by side grafting. To optimize cocoa rejuvenation and minimize WF, it is crucial to carefully select the appropriate nursery technique. Further evaluation is necessary to explore the potential benefits of implementing precision irrigation techniques to reduce WF during the nursery phase. By focusing on sustainable nursery practices, we can enhance the overall sustainability of cocoa production.